The Influence of Technological Advancements in Inventory Control on Distribution Efficiency and Customer Satisfaction: A Systematic Literature Review - Hasahatan, Anuar; Maniah; Waskito, Saptono Kusdanu (International Journal of Science and Society, 2025)
In today fast paced and technological era and sophisticated distribution environment, an effective inventory management is important to achieve operational excellence and ensuring customer satisfaction. This study provides a review of existing literature on how technological advancements have revolutionized inventory control in distribution and effects to its customer satisfaction. Using the PRISMA method, we analyzed 61 peer-reviewed articles published between 2015 and 2025 to understand the impact of these technologies on distribution efficiency and customer outcomes. The findings consistently show that adopting AI, RFID, Blockchain and IoT systems significantly enhances operational performance by improving inventory visibility, reducing lead times, minimizing errors, and enabling real-time decision-making. These improvements lead to higher levels of customer satisfaction so it can give more accurate deliveries, quicker response times, and improved service reliability.